Implementasi Pembelajaran Bahasa Inggris dengan Media Kartu Gambar di SD Negeri 1 Kadipaten Tasikmalaya Kelas IV - Cica Mubarakatu Zakia; Erwin Rahayu Saputra (Jurnal Sekolah Dasar, 2023)
This study aims to determine the ability of students to understand learning English in the application of the 2013 curriculum using picture media at SD Negeri 1 Kadipaten Tasikmalaya class IV. Learning media is an important component in the learning process in order to achieve learning objectives. The learning media used in this study is using media images which are expected to train students' cognitive abilities in memorizing English vocabulary using media images. Where the number of grade IV students at SD Negeri 1 Kadipaten is 48 people, 10 female students and 40 male students. This research is a type of qualitative research and data collection techniques in this study are through observation and documentation. In this study, students were very enthusiastic in participating in the learning process. We know that in the 2013 curriculum learning English was abolished, this became a trigger for students' learning motivation in learning English. Thus this teaching practice research can be said to be successful in improving students' ability to know and understand English vocabulary through the media of pictures.